Tensile, electrical properties and morphology of polyethylene/modified fly ash composites using ultraflow - Chinh, Nguyen Thuy; Mai, Tran Thi; Thu Trang, Nguyen Thi; Giang, Nguyen Vu; Trung, Tran Huu; Thanh Huong, Nguyen Thi; Hoang, Thai (Vietnam Journal of Chemistry, 2016)
This paper presents relative melt viscosity, tensile, electrical properties and morphology of high density polyethylene (HDPE)/organo-modified fly ash (MFA) and HDPE/MFA/ultraflow (UTF) composites which were prepared by melt mixing method. Relative melt viscosity of HDPE was decreased with adding MFA and UTF into HDPE. Tensile properties (tensile strength, elongation at break and Young’s modulus) of HDPE/MFA/UTF composites were increased with rising UTF content to 5 wt.% and thereafter, they were dropped with the UTF content more than 5 wt.%. Electric properties (dielectric constant, dielectric loss and volume resistivity) of the HDPE/MFA and HDPE/MFA/UTF composites were investigated. The obtained parameters showed that the HDPE/MFA composites have electric insulation higher than HDPE/MFA/UTF composites. Morphology of the composite materials with and without using UTF was also studied by Field Emission Scanning Electron Microscopy (FESEM) images. The results indicated that the MFA was dispersed more regularly and less agglomerated in HDPE matrix with adding UTF into the HDPE/MFA composites.